2009
DOI: 10.1038/bmt.2009.64
|View full text |Cite
|
Sign up to set email alerts
|

Non-intensive treatment with low-dose 5-aza-2′-deoxycytidine (DAC) prior to allogeneic blood SCT of older MDS/AML patients

Abstract: Novel, non-intensive treatment options in older MDS/ AML patients planned for allografting, with the goal of down-staging the underlying disease and bridging time to transplantation, are presently being developed. 5-azacytidine and decitabine (DAC) are of particular interest, as they can be given repetitively, with very limited nonhematologic toxicity and result in responses both in MDS and AML even at low doses. We describe 15 consecutive patients (median age 69 years, range 60-75 years) with MDS (n ¼ 10) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…21 Another study reported that almost all of the 10 MDS patients who were treated with DEC and underwent subsequent alloHCT after reduced-intensity conditioning, achieved successful engraftment and CR. 22 A recent retrospective analysis showed that pre-alloHCT HMT induced rapid and high level of donor chimerism. 23 All the results indicated that HMT as a bridge to alloHCT was feasible in patients who subsequently received alloHCT.…”
Section: Discussionmentioning
confidence: 99%
“…21 Another study reported that almost all of the 10 MDS patients who were treated with DEC and underwent subsequent alloHCT after reduced-intensity conditioning, achieved successful engraftment and CR. 22 A recent retrospective analysis showed that pre-alloHCT HMT induced rapid and high level of donor chimerism. 23 All the results indicated that HMT as a bridge to alloHCT was feasible in patients who subsequently received alloHCT.…”
Section: Discussionmentioning
confidence: 99%
“…A CR was defined as o5% blasts in a BM of adequate cellularity and no Auer rods, absence of leukemic blasts in the peripheral blood, an ANC of ⩾ 1000/μL, platelets of ⩾ 100 000/μL and transfusion independence. 9 Patients not fulfilling CR criteria were scored as having achieved temporary disease control when the mixed chimerism in the peripheral blood remained stable, without evidence of increasing leukocytosis, for at least 4 weeks (chimerism was routinely monitored every 1-2 weeks in the peripheral blood). Patients were scored as treatment failure when no temporary disease control was achieved.…”
Section: Response Criteria and Evaluationmentioning
confidence: 99%
“…A CR was defined as o5% blasts in a BM of adequate cellularity and no Auer rods, absence of leukemic blasts in the peripheral blood, an ANC of X1000/ml, plts of X100 000/ml and transfusion independence. 19 Patients not fulfilling CR criteria were scored as having achieved temporary disease control when the mixed chimerism in the peripheral blood remained stable, without evidence of increasing leukocytosis, for at least 4 weeks (chimerism was routinely monitored every 1-2 weeks in the peripheral blood). When no temporary disease control was achieved, the patient was scored as a treatment failure.…”
Section: Response Criteria and Evaluationmentioning
confidence: 99%